A Retrospective Report on the Infestation and Distribution of Chiggers on an Endemic Rodent Species (Apodemus latronum) in Southwest China - Qiao-Yi Liu; Xian-Guo Guo; Rong Fan; Wen-Yu Song; Pei-Ying Peng; Ya-Fei Zhao; Dao-Chao Jin (Veterinary Sciences)
Chiggers are the exclusive vector of Orientia tsutsugamushi, which is the causative agent of scrub typhus. Based on the field surveys in southwest China between 2001 and 2022, this paper retrospectively reported the chigger infestation and distribution on the large-eared field mouse (Apodemus latronum), an endemic rodent species in the region, for the first time. A total of 933 chiggers were collected from 501 mice, and these chiggers were identified as 2 families, 8 genera, and 61 species. The overall infestation prevalence (PM) and mean abundance (MA) of A. latronum with chiggers reached 19.76% and 1.86 mites/per mouse, respectively. The chigger infestation indices on adult A. latronum (PM = 38.28%, MA = 5.11) were higher than those on juvenile mice (PM = 12.63%, MA = 0.97) with p < 0.01, showing an age bias of infestation. The relative fatness (K) was used to reflect the nutrition status of the mouse host. The mouse hosts with good nutrition (K = 3.4 ± 0.89 g/cm3) harbored fewer chiggers than the hosts with poor nutrition (K = 2.2 ± 0.90 g/cm3) (p < 0.01). The infestation indices of chiggers on A. latronum obviously fluctuated along different altitude gradients (p < 0.01). With the increase in altitudes, the β diversity of the chigger community showed a gradually increasing tendency. The spillover chord diagram, which was based on indices of PAC (potential for apparent competition), revealed high spillover potentials of dominant chigger species dispersing from high altitude gradients to the lowest one. The chigger abundance was positively correlated with the mean monthly temperature (tmp), mean monthly humidity (hum), the mean monthly precipitation (pre), and the human footprint (hfp), and it was negatively correlated with the altitude (ele) (p < 0.05). The temperature and humidity are the most important factors which influence the chigger infestation.